Re-irradiation after gross total resection of recurrent glioblastoma: Spatial pattern of recurrence and a review of the literature as a basis for target volume definition Rebestrahlung nach kompletter Resektion eines rezidivierten: Glioblastoms Räumliches Rezidivmuster und Review der Literatur als Grundlage für das Zielvolumen - Straube, Christoph; Elpula, Greeshma; Gempt, Jens; Gerhardt, Julia; Bette, Stefanie; Zimmer, Claus; Schmidt-Graf, Friederike; Meyer, Bernhard; Combs, Stephanie E. (Strahlentherapie und Onkologie, 2017)
Background Currently, patients with gross total resection (GTR) of recurrent glioblastoma (rGBM) undergo adjuvant chemotherapy or are followed up until progression. Re-irradiation, as one of the most effective treatments in macroscopic rGBM, is withheld in this situation, as uncertainties about the pattern of re-recurrence, the target volume, and also the efficacy of early re-irradiation after GTR exist. Methods Imaging and clinical data from 26 consecutive patients with GTR of rGBM were analyzed. The spatial pattern of recurrences was analyzed according to the RANOHGG criteria (“response assessment in neuro-oncology criteria for high-grade gliomas”). Progression-free (PFS) and overall survival (OS) were analyzed by the Kaplan-Meier method. Furthermore, a systematic review was performed in PubMed. Results All but 4 patients underwent adjuvant chemotherapy after GTR. Progression was diagnosed in 20 of 26 patients and 70% of recurrent tumors occurred adjacent to the resection cavity. The median extension beyond the edge of the resection cavity was 20 mm. Median PFS was 6 months; OS was 12.8 months. We propose a target volume containing the resection cavity and every contrast enhancing lesion as the gross tumor volume (GTV), a spherical margin of 5-10mm to generate the clinical target volume (CTV), and a margin of 1-3mm to generate the planning target volume (PTV). Re-irradiation of this volume is deemed to be safe and likely to prolong PFS. Conclusion Re-irradiation is worth considering also after GTR, as the volumes that need to be treated are limited and re-irradiation has already proven to be a safe treatment option in general. The strategy of early re-irradiation is currently being tested within the GlioCave/NOA 17/Aro 2016/03 trial.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Glioblastoma; Pattern of recurrence; Recurrence; Survival; Target volume